Efektifitas Penggunaan Media Kotak Alfabet dan Gambar Terhadap Kemampuan Membaca Siswa Kelas II SDN 1 Kertayasa - Rita Kusumah; Anisya, Rachma (Jurnal Lensa Pendas, 2024)
This study aims to determine the Effectiveness of the Use of Alphabet Boxes and Pictures on the Reading Ability of Class II Students of SDN 1 Kertayasa. Where reading is one of the abilities that students must have in the educational process. Reading can be a bridge for students who wish to progress and succeed both in the family, school and community. This research is a pre-experimental study with a One Group Pretest-Posttest design. The population in this study were all class II students at SD Negeri 1 Kertayasa, totaling 26 students. The sampling technique in this study is total sampling. Data collection techniques used in this study were interviews, observations, tests, and documentation. The data analysis technique used in this study is the normality test, homogeneity test, and hypothesis testing (Wilcoxon). The results of the study showed that (1) Before using Alphabet Box Media and Pictures in class II students of SD Negeri 1 Kertayasa they were still lacking with an average value of 53,46. (2) After using the Alphabet Box Media and Pictures in class II students of SD Negeri 1 Kertayasa experienced an increase with an average value of 83,46. (3) There is an influence in using Alphabetical Box Media and Pictures in class II students of SD Negeri 1 Kertayasa with an Asymp.Sig value. (2-taied) 0.000.